(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
India’s nuclear doctrine, based on Credible Minimum Deterrence (CMD) and No First Use (NFU), aims to maintain deterrence stability while minimizing escalation risks. However, evolving regional threats—such as Pakistan’s full-spectrum deterrence and China’s strategic modernization—have challenged its sustainability. This study, using qualitative analysis of policy documents, strategic literature, and expert views, examines tensions within India’s nuclear strategy, including ambiguity in retaliatory posture, pre-emption risks, second-strike credibility, and ballistic missile defence. While India remains officially committed to NFU, recent statements indicate a shift toward greater strategic flexibility to enhance deterrence credibility—potentially heightening escalation risks. The paper argues that India’s doctrine is at a crossroads, requiring doctrinal clarity, robust command and control, enhanced survivability, and transparent signalling to maintain stability. The findings inform broader debates on nuclear deterrence and escalation control in Southern Asia and underscore the need for responsible nuclear stewardship.